Prediction of maternal near-miss in placenta previa: a retrospective analysis from a tertiary center in Ankara, Turkey. (1st February 2018) - Coskun, Bora; Akkurt, Iltac; Dur, Rıza; Akkurt, Mehmet O.; Ergani, Seval Y.; Turan, Ozerk T.; Coskun, Bugra
Abstract: Aim: To determine risk factors for severe complications during and after cesarean delivery (CD) in placenta previa (PP). Methods: We reviewed retrospectively collected data from women with PP who underwent CD during a 6-year study period. We identified the complicated group based on the modified WHO near-miss criteria. Complicated and noncomplicated groups were compared considering clinical, laboratory, and sonographic features. Results: Thirty-seven of 256 cases classified as near miss consisting of 14 peripartum hysterectomies, 12 uterine balloon placements, 10 great artery ligations, and four B-lynch suture placement procedures without maternal mortality. Perioperative complications included surgical wound infections ( n  = 5), bladder injury ( n  = 4), pelvic abscess ( n  = 1), and uterine rupture ( n  = 1). Logistic regression analyses demonstrated following features to be associated with maternal near miss in PP: (1) coexistent abruption (aOR 13.2, 95% CI 5.8–75.3), (2) morbidly adherent placenta (aOR 11.92, 95% CI 3.24–43.82), (3) number of hospitalizations for vaginal bleeding (≥3) (aOR 8.88, 95% CI 3.32–26.69), and (4) transvaginal cervical length (CL) measurement <10th percentile (aOR 5.5, 95% CI 2.1–15.4). Conclusion: Short cervical length, recurrent vaginal bleeding, morbidly adherent placenta, and concurrent placental abruption are independent predictors for subsequent severe maternal morbidity in PP cases. Early identification of these risk factors during PP follow-up may improve maternal outcome.